Eine kurze Geschichte der deutschsprachigen Science Fiction - Hans Esselborn (Recherches Germaniques)
The history of German science fiction started at the end of the 19th century with Kurd Laßwitz’s ‘scientific tales’ and his novel Auf zwei Planeten. This literature blossomed with science fiction novels, short stories and thin booklets up to the First World War and attained an international peak with Hans Dominik and the avant-gardist Alfred Döblin in the Weimar Republic. After the Second World War, there was an ideological split between West and East German literature although they dealt with similar topics like the atomic disaster. Since the sixties, a strong Anglo-American influence has been felt on science fiction literature so that it is even possible now to talk of a global form of science fiction literature. After this, three generations of writers emerged, partly shaped by cybernetics, the fantastic, pop, cyberpunk and postmodernism. I will focus on Herbert W. Franke and Dietmar Dath as representing the elder and the younger generation respectively.